Técnicas de aprendizaje y el rendimiento académico de lengua y literatura. - Gutiérrez Salabarria, Judith Alexandra (2021)
The research starts from the scientific problem. How to improve the academic performance of the students in the subject Language and Literature? and it is determined as general objective: To develop learning techniques to improve academic performance in the subject of Language and Literature of the students of the "Celeste Carlier" Basic Education School in Quevedo canton, Los Ríos province. A mixed approach and applied research are used and from this methodological reference theoretical, empirical and statistical methods are used, which allowed to conclude that: The study of scientific literature allowed to base learning techniques and academic performance from the epistemological point of view, find the indicators to carry out the diagnosis and support the proposal; The diagnosis made on the learning techniques in the subject of Language and Literature allowed to reveal deficiencies in reading that affect academic performance and the design of learning techniques to improve the academic performance of students was validated through the criteria of specialists , the socialization workshop allowed to demonstrate its validity and relevance and the partial incursion into practice allowed to corroborate the feasibility of the techniques for learning the subject Language and Literature in Basic Education and consider it an alternative to improve academic performance